ROMBONGAN PERKEBUNAN PARAKAN SALAK SUKABUMI DI AMSTERDAM TAHUN 1883: GAMELAN PARAKAN SALAK - Nugraha, Asep (LP2M ISBI Bandung, 2018)
In 1883 the tea _plantation in the Parakan Salak Sukabumi region brought workers from the local plantation community to Amsterdam, to participated in De Internationale Koloniale en Uitvoerhandel Tentoonstelling. Planter, Mr. Holle, promoted the commodity of tea by including the original culture of the land of the colony, precisely the Sundanese ethnicity. Sundanese cultural presentations include gamelan and dance performances and cultural tours of Sundanese villages. The moment was the first time Europeans directly witnessed people from the colonies played music and danced and carried out activities of daily life through village activities. This paper describes the existence of the Parakan Salak plantation group in Amsterdam in 1883.